2013
DOI: 10.3390/ijms140611560
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Regulated Protein-Protein Interaction Networks and Their Functions in Breast Cancer

Abstract: MicroRNAs, which are small endogenous RNA regulators, have been associated with various types of cancer. Breast cancer is a major health threat for women worldwide. Many miRNAs were reported to be associated with the progression and carcinogenesis of breast cancer. In this study, we aimed to discover novel breast cancer-related miRNAs and to elucidate their functions. First, we identified confident miRNA-target pairs by combining data from miRNA target prediction databases and expression profiles of miRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Transcriptional regulator megakaryoblastic leukemia-1-induced tenascin-C and SAP domain are key players for breast cancer progression and migration 77. The association between let-7c, miR-125a-5p, miR-125b-5p, and miR-21-5p and breast cancer was revealed 78. E26 transformation-specific (ETS) transcription factor regulate the expression of genes involved in biological processes.…”
Section: Othersmentioning
confidence: 99%
“…Transcriptional regulator megakaryoblastic leukemia-1-induced tenascin-C and SAP domain are key players for breast cancer progression and migration 77. The association between let-7c, miR-125a-5p, miR-125b-5p, and miR-21-5p and breast cancer was revealed 78. E26 transformation-specific (ETS) transcription factor regulate the expression of genes involved in biological processes.…”
Section: Othersmentioning
confidence: 99%
“…Interestingly, TGFB also cross-talks with several other pathways, including estrogen receptor signaling (Matsuda et al 2001), which have also been identified as miR-139-5p targets from our analyses. Also interestingly, proteins underlying this pathway were identified to be potentially regulated by miR-139-5p using target prediction software (Lee et al 2013).…”
Section: Mir-139-5p Targets Genes Involved In Pathways Associated Witmentioning
confidence: 99%
“…This miRNA has been found to be down regulated in testicular embryonic carcinoma, hepatocellular carcinoma, glioma, medulloblastoma, 15,16 breast cancer, 17 and ependymoma. 18 Results of a study showed that exposure to UV led to a significantly lower expression of miR-383 in A431cells (a model human cell line of epidermoid carcinoma).…”
Section: Introductionmentioning
confidence: 99%